The Role Of The Concept Of Innovative Development In The Education Of The Third Renaissance - Turdiyev Bahritdin Samiyevich (Zien Journals, 2021)
The article scientifically analyzes the role of the concept of innovative development in the education of youth of the third Renaissance. The national innovation system serves as the basis for the development of the economy between science, industry and society, and the needs of innovative development determine and stimulate the development of scientific activity
Keywords: Innovation; activity; science; state